2012
DOI: 10.4314/wsa.v35i2.76756
|View full text |Cite
|
Sign up to set email alerts
|

Full-scale trials of external nitrification on plastic media nitrifying trickling filter

Abstract: The full-scale single-stage tertiary nitrifying trickling filter (NTF) at the Citrusdal Wastewater Treatment Plant provides for external nitrification of unclarified effluent from the facultative aerobic lagoon in order to meet standard effluent ammonia concentration requirements. The apparent ammonia nitrification rate (ApANR, gN/m 2 media surface•d) of the NTF was sensitive to particulate organic loading rates which were predominantly in the form of algae, and the soluble COD removal rates increased under co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 8 publications
(18 reference statements)
0
7
0
Order By: Relevance
“…The lower nitrification efficiency obtained for higher SB is attributed to the increasing particulate and soluble COD concentration in the nitrifying TF influent (second stage TF). The importance of maintaining low influent suspended solids and biodegradable organic matter to achieve good performance in nitrifying TFs has been previously reported (Parker et al, 1989;Parker et al, 1995;Mofokeng et al, 2009;Dai et al, 2013). In these investigations, it has been suggested that the influence of influent biodegradable organic matter on nitrification is due to the development of a heterotrophic population, which competes with the nitrifiers for oxygen, thereby reducing nitrification rates.…”
Section: Performance Of the Anaerobic-anoxic Modified Primary Clarifier With Sludge Bypass To The First Trickling Filtermentioning
confidence: 94%
“…The lower nitrification efficiency obtained for higher SB is attributed to the increasing particulate and soluble COD concentration in the nitrifying TF influent (second stage TF). The importance of maintaining low influent suspended solids and biodegradable organic matter to achieve good performance in nitrifying TFs has been previously reported (Parker et al, 1989;Parker et al, 1995;Mofokeng et al, 2009;Dai et al, 2013). In these investigations, it has been suggested that the influence of influent biodegradable organic matter on nitrification is due to the development of a heterotrophic population, which competes with the nitrifiers for oxygen, thereby reducing nitrification rates.…”
Section: Performance Of the Anaerobic-anoxic Modified Primary Clarifier With Sludge Bypass To The First Trickling Filtermentioning
confidence: 94%
“…However, when operated as single units and at half the NH3 loading rate, the performance deteriorated. In a third comparative study, Mofokeng et al (2009) investigated both a full-scale and lab-scale NTF (each a single reactor) treating effluent from a partially aerated lagoon. The NTFs had an area:height ratio of 5.6 and 0.014, respectively.…”
Section: Ntf Performancementioning
confidence: 99%
“…While quality empirical data sets from pilot and/or full scale operations are available (e.g. Andersson et al, 1994;Boiler and Gujer, 1986;Goldstein and Smith, 2002;Gullicks and Cleasby, 1986;Mofokeng et al, 2009;Parker et al, 1995;Parker et al, 1989;Parker et al, 1997), of the extensive data sets that were reviewed, only those published by Parker and coworkers include detailed kinetic data within the NTF. The value and importance of such kinetic data within the depths of an NTF relates to the ability to refine and optimize the empirical-based design of full-scale NTFs for site-specific conditions; the NTF design models all integrate and require zero-and first-order NH3 : emoval kinetic parameters.…”
mentioning
confidence: 99%
“…The remaining fractions were not much affected by the polymer treatment. Mofokeng et al (2009) investigated the full-scale singlestage tertiary nitrifying trickling filter at the Citrusdal wastewater treatment plant. The filter provides for external nitrification of unclarified effluent from the facultative aerobic lagoon in order to meet standard effluent ammonia concentration requirements.…”
Section: Water Treatmentmentioning
confidence: 99%